KETAHANAN PANGAN MELALUI BUDIDAYA IKAN AIR TAWAR SISTEM BIOFLOK - Dedi - Kusmayadi (Jurnal Pasca Dharma Pengabdian Masyarakat, 2022)
This activity is a continuation of the previous year's community service program which aims to improve food security capabilities independently through the development of biofloc freshwater fish farming systems, especially for community groups affected by the COVID-19 pandemic located in Pamegatan Hamlet, Manonjaya District, Tasikmalaya Regency which in previous programs have received training on cultivation. This follow-up program focuses on solving problems that occurred in the previous program, namely (1) there is still a lack of public knowledge about water treatment for alum aquaculture with the biofloc system, (2) the high mortality rate of fish caused by poor water quality in ponds, (3) the price of fish seeds is relatively expensive. From these problems, a mentoring program was created that involved biofloc experts for six months. The assistance includes (1) providing knowledge about water conservancy in order to improve water quality for fish farming with biofloc systems through the creation of a pond filtration system, (2) providing training on fish care in biofloc system cultivation and making probiotics along with fish natural medicine (3) making ponds. fish nurseries to produce seeds independently. The results of the activity show that the biofloc system of freshwater fish farming has been successful and has been able to provide benefits to communities affected by the COVID-19 pandemic, as evidenced by the abundant first harvest